Book Review: Greenwood, M. et al. (Eds.). (2015). Determinants of Indigenous Peoples' Health in Canada: Beyond the Social - Mignone, Javier (International Indigenous Policy Journal, 2017)
This article provides a review of the book Determinants of Indigenous Peoples’ Health in Canada: Beyond the Social edited by Margo Greenwood, Sarah de Leeuw, Nicole Marie Lindsay, and Charlotte Reading.